ANALYSIS OF THE PROBLEMS FACED BY TEACHERS IN THE WORLD OF EDUCATION - Fitriani, Irma; Azzahro, Azkia Adilla; Arrapi, M Syahrin; Hakim, Fazikri; Rahwaniko, Hasri (Proceeding International Seminar of Islamic Studies, 2023)
In the world we face, not far from the word problem, the emergence of a problem so that we can observe and learn more from what we have experienced, in the end we want to study and evaluate it so that the problem will not continue in the future, no wonder in the world of education that the problems in education are also very deep with the conditions that we have experienced during the corona time we have to undergo online learning but now everything has returned to where we also have to pay attention to the problems that exist in the world of education so that learning does not run away from the educational goals Alone, one of them is the problems faced by teachers in the world of education itself, the method we do is descriptive qualitative research by collecting data publicly through journals related to the title of the material we will examine. The results of our research show that the world of education also has its own problems, both from teachers and students, which we also have to have solutions to deal with.